Vision recovery after ocular massage for cosmetic filler-induced ophthalmic artery occlusion - Alexander A. Svoronos; Nathan L. Scott (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of vision recovery after ocular massage for cosmetic filler-induced ophthalmic artery occlusion. Observations: A 58-year-old female experienced acute loss of vision of the left eye, left ptosis, and left glabellar skin discoloration immediately after cosmetic filler injection, suggestive of occlusion of the branches of the ophthalmic artery. Highly aggressive, prolonged ocular massage was initiated soon after and followed by a substantial recovery of vision. In the following days, signs of anterior segment ischemia and choroidal infarcts developed. Additionally, extramacular preretinal hemorrhages emerged, presumably from shearing of retinal capillaries during the ocular massage. These findings resolved without significant permanent visual deficits. Conclusions and Importance: We report a unique case of vision recovery after ocular massage in the setting of arterial occlusion due to cosmetic filler injection. It is also a rare case of preretinal hemorrhages associated with ocular massage. The case suggests that ocular massage might, at least in rare circumstances, be effective for treating cosmetic filler-induced retinal artery occlusion.